PAIN: PSYCHOLOGICAL ASPECTS - V. V. Osipova (Неврология, нейропсихиатрия, психосоматика)
The psychological factors that determine an individual predisposition to pain syndromes, the specific features of pain experience and pain behavior, as well as choice of pain relief strategies are considered. Particular emphasis is on the association between pain and depression.